Synthesis compound XCR-7a ameliorates LPS-induced inflammatory response by inhibiting the phosphorylation of c-Fos - Haimei Tang (Elsevier, 2022)
Inflammation is a biological process closely related to different kinds of diseases, such as cancer and metabolic diseases. Therefore, effective control of the occurrence and development of inflammation is of great significance for disease prevention and control. Recently, 2-substituted indoles have gradually become a research hotspot because of their stability and pharmacological activity. Here we synthesized a series of compound containing 2-substituted indoles and investigated XCR-7a’s role in inflammatory response. Our data show that XCR-7a can inhibit the production of inflammatory cytokines interleukin-1 beta (IL-1β), interleukin-6 (IL-6) and inflammatory mediator cyclooxygenase-2 (COX-2) induced by lipopolysaccharide (LPS) in mouse peritoneal macrophages. Also, XCR-7a has a protective effect on LPS-induced inflammatory response in mice. Mechanically, we found that XCR-7a could inhibit the phosphorylation of c-Fos induced by LPS, which suggested that the protective effect of XCR-7a on inflammation was related to its negative regulation to phosphorylation of c-Fos. Briefly, our results demonstrated that XCR-7a could be expected to be a potential drug for controlling inflammation.